β-lactam and tetracycline residues in fresh milk acquired by the Glass of Milk Committees of the San Jerónimo and Andahuaylas districts in Apurímac, Peru - Choque-Quispe, David (2020)
The aim of this study was to evaluate the effect of the presence of residues of β- lactam antibiotics and tetracyclines, as well as the physicochemical properties of fresh milk acquired by the Glass of Milk Committees of two districts of Apurimac, Peru. Triplicate milk samples were analyzed from 37 and 32 committees in the districts of San Jerónimo and Andahuaylas respectively. Density, acidity, pH, total solids (TS) and alcohol test were determined and compared with the Peruvian Technical Standards (NTP) for fresh milk. The presence of β-lactam and tetracycline antibiotic compounds was determined through the Betastar® colorimetric kit. The physicochemical properties were correlated with the presence of antibiotics through the Pearson coefficient. A principal component analysis (PCA) was performed. Results showed that 10.8% of the milk samples from the San Jerónimo committees were positive for tetracycline, while 9.4 and 3.1% of the San Jerónimo and Andahuaylas committees, respectively, were positive for β-lactams. A high percentage of milk samples were outside the ranges established by the NTP for density, pH, acidity and TS. The PCA analysis shows that acidity and density are the main variables that would would determine the presence of antibiotics.